موقع معطيات اقتصاد المعرفة ضمن الاستراتيجيات التنافسية للمؤسسة - كبيري, فتيحة; سماحي, أحمد (Université de M'sila, 2017)
The paradigm shift and the rapid changes in the economy, in thought and practice. Able to change the status of the economy of the industrialized economy doomed patterns and absorbing and laws familiar to some extent with the institution, to a knowledge economy and the main its key strategic knowledge in all derivatives of technology, information and communication. This institution was forced to research and re-create a new environmental path and its own in this novel data. Especially the environment as much as reinforced opportunities including, met with the dangers and threats of more and faster impact on the life of the institution. In the end, it is more than ever demanding satisfaction of all parties to this environment, starting the big competitive intensity prevailing within it. On the other hand, in light of the abolition of all protectionist restrictions that were protecting institutions in many economies, in response to the global economic openness in all its practices, trade, productivity and others. The institution was forced to rework their strategies within this competitive market.
Keywords: knowledge economy, information, technology, competitive, and competitive strategies.